2022
DOI: 10.1186/s13075-022-02783-0
|View full text |Cite
|
Sign up to set email alerts
|

Systemic sclerosis and pregnancy outcomes: a retrospective study from a single center

Abstract: Background Pregnancy in systemic sclerosis (SSc) patients is no more an infrequent event as it used to be, but literature data on pregnancy outcomes in women with SSc are scarce. The rate of preterm deliveries and intrauterine growth restriction (IUGR) seems to be increased, while the risk of miscarriages is controversial. Moreover, no study compared pregnancy outcomes in SSc with antiphospholipid syndrome (APS) and systemic lupus erythematosus (SLE). We performed a retrospective study to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…It is well-known that APS, especially accompany with thrombophilia, is frequently associated with pregnancy complications such as preeclampsia, recurrent miscarriage, and premature birth [17]. Our research suggests that hypertension during pregnancy is a risk factor of adverse outcomes in pregnant APS women, which is consistent with the results of previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…It is well-known that APS, especially accompany with thrombophilia, is frequently associated with pregnancy complications such as preeclampsia, recurrent miscarriage, and premature birth [17]. Our research suggests that hypertension during pregnancy is a risk factor of adverse outcomes in pregnant APS women, which is consistent with the results of previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…Research on pregnancy outcomes in rare systemic autoimmune RDs has shown increased rates of various maternal and neonatal complications, depending on the specific diagnosis. 11,15,[111][112][113][114][115][116] A 2020 systematic literature review and meta-analysis found that systemic sclerosis may increase the risk of gestational hypertension, miscarriage, IUGR, low birth weight, C-section and preterm delivery; however, the data do not allow firm conclusions to be drawn regarding the relationship between pregnancy and disease worsening or improvement. 111 A 2018 United…”
Section: Other Rheumatic Diseasesmentioning
confidence: 99%